2015
DOI: 10.3758/s13421-015-0519-1
|View full text |Cite
|
Sign up to set email alerts
|

Remembering the melody and timbre, forgetting the key and tempo

Abstract: The identity of a melody is independent of surface features such as key (pitch level), tempo (speed), and timbre (musical instrument). We examined the duration of memory for melodies (tunes) and whether such memory is affected by changes in key, tempo, or timbre. After listening to previously unfamiliar melodies twice, participants provided recognition ratings for the same (old) melodies as well as for an equal number of new melodies. The delay between initial exposure and test was 10 min, 1 day, or 1 week. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(65 citation statements)
references
References 57 publications
9
55
0
Order By: Relevance
“…The present research focused on musical timbre and instrumentation, which has been identified as a particularly important surface feature influencing the ability to remember music (Halpern & Müllensiefen, 2008;Poulin-Charronnat et al, 2004;Schellenberg & Habashi, 2015;Trainor et al, 2004). For example, research shows that participants' long-term memory for music deteriorates significantly when the instrumentation used at the recognitions test phase does not match the one used at the learning phase (Halpern & Müllensiefen, 2008;Poulin-Charronnat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The present research focused on musical timbre and instrumentation, which has been identified as a particularly important surface feature influencing the ability to remember music (Halpern & Müllensiefen, 2008;Poulin-Charronnat et al, 2004;Schellenberg & Habashi, 2015;Trainor et al, 2004). For example, research shows that participants' long-term memory for music deteriorates significantly when the instrumentation used at the recognitions test phase does not match the one used at the learning phase (Halpern & Müllensiefen, 2008;Poulin-Charronnat et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It is also unknown whether tempo changes smaller than 15-20% could impair melody recognition. In previous research, moreover, novel melodies were very short in duration (i.e., 4-10 s; Halpern & Müllensiefen, 2008;Kleinsmith & Neill, 2018), or longer but with a simple structure (AA'BA'- Schellenberg et al, 2014;Schellenberg & Habashi, 2015;AA'-Schellenberg et al, 2017), and much repetition within each melody. Thus, it is an open question whether previous findings would generalize broadly.…”
mentioning
confidence: 89%
“…timbre; Schellenberg & Habashi, 2015). For example, it is relatively easy to imagine hearing The Star-Spangled Banner performed on a tuba, at a very low pitch, and at a very slow tempo.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another study, comparing intensity and consonance shows that intensity was the more significant determinant of preference; the effect of dissonance on preference was negligible (Martindale & Moore, 1990). About the importance of pitch, tempo, and timber in a melody, a study shows the timber of melody is more kept in our memory than pitch and tempo, though melody identification is independent of the mentioned surface features (Schellenberg & Habashi, 2015). Although many paper reviews summarize the influential factors on music preferences like tempo, rhythm, pitch, harmony, and loudness (LeBlanc, 1981;North & Hargreaves, 2008), some paper reviews make their endeavors to provide an order for the influential factors on musical preferences.…”
Section: Basic Musical Attributes-basic Layermentioning
confidence: 99%